DEVELOPMENT OF INDEPENDENT WORK COMPETENCIES OF “TEMURBEKLAR MAKTABI” STUDENTS BY MEANS OF ELECTRONIC EDUCATIONAL RESOURCES (American Journal of Pedagogical and Educational Research, 2024)
This article talks about the development of independent work competencies of the students of “Temurbeklar maktabi” military academic lyceum with the help of electronic educational resources, as well as information about the types, possibilities, and development of electronic educational resources.